ANALISIS STRATEGI PEMASARAN ANSOFF MATRIX DALAM MENINGKATKAN PENJUALAN PADA USAHA RUMAH MAKAN DENDENG BATOKOK DI JALAN RUMAH SAKIT HAJI MEDAN - Muhammad Ihza Hasibuan; Ali Fikri Hasibuan (STKIP Subang, 2026)
Increasingly fierce competition in the culinary business requires entrepreneurs to implement appropriate and sustainable marketing strategies to increase sales. This study aims to analyze the application of Ansoff Matrix-based marketing strategies in increasing sales at Rumah Makan Dendeng Batokok, located on Jalan Rumah Sakit Haji Medan. This study uses a qualitative approach with a case study method. Data collection was conducted through in-depth interviews with business owners, employees, and customers, direct observation, and documentation. Data analysis was performed thematically using the Miles and Huberman interactive model with the assistance of NVivo 15 software. The results showed that market penetration was the most dominant strategy applied, through consistency in taste, improved service quality, cleanliness, and simple promotion through social media, which contributed to increased customer loyalty and sales stability. Product development was carried out by adding menu variety and product innovation to increase consumer appeal. The market development strategy was implemented through the opening of new branches, which successfully expanded market share and increased the number of customers. Meanwhile, the diversification strategy is still in the planning stage due to limited capital and resources. Overall, the application of a combination of strategies in the Ansoff Matrix has proven to contribute positively to increased sales and strengthened competitiveness for Rumah Makan Dendeng Batokok amid competition in the culinary industry. Keywords: marketing strategy, Ansoff Matrix, sales, culinary business, NVivo 15.